OBSERVATIONS ON THE LOBSTERS OF MINICOY ATOLL - Pillai, C S Gopinatha; Mohan, Madan; Kunhikoya, K K (Indian Journal of Fisheries, 2011)
The rock-lobsters Panulirus penicillatus, P. homariis and P. versicolor occur in Minicoy. P. versicolor, now the most common, is possibly a recent arrival as this species has not been previously recorded from here. The spatial distribution, social behaviour, local migration on the reef flats, specific habitat selection and juvenile recruitment of the species in the atoll are discussed.